Wear-resistant heat-dissipating rubber masterbatch and preparation method thereof

By premixing materials such as carbon black and dispersed fibers in paraffin, wear-resistant heat-dissipating rubber masterbatches are prepared, which solves the problems of poor dispersion of additives and dust pollution in the prior art, and achieves high wear resistance and heat dissipation of rubber.

CN114752085BActive Publication Date: 2025-04-04XIONGXIAN JIANGYUAN MASTERBATCH MANUFACTURING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202210443068.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-25
Publication Date
2025-04-04
Estimated Expiration
2042-04-25

AI Technical Summary

Technical Problem

When the prior art improves the wear resistance and heat dissipation performance of rubber, it is difficult to effectively disperse powdered additives, resulting in poor wear resistance and heat dissipation effects, and a large amount of dust is generated during the intensive processing, affecting the environment.

Method used

By pre-mixing and stirring materials such as aromatic oil, carbon black, white carbon black, etc., it becomes dense, and combined with aluminum silicate staple fibers, polytetrafluoroethylene staple fibers and micro-scale ceramic powder and metal aluminum powder are dispersed in paraffin, and granulated in a screw extruder using ethylene-vinyl acetate copolymer to prepare wear-resistant heat dissipation rubber masterbatches.

Benefits of technology

It significantly improves the dispersion of additives in rubber, enhances wear resistance and heat dissipation effects, reduces the generation of dust during dense processing, and improves the processing environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114752085B_ABST
    Figure CN114752085B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of functional polymer materials, and discloses a wear-resistant and heat-dissipating rubber masterbatch and a preparation method. Aromatic oil is used to pre-treat carbon black and white carbon black as material A, so that the fluffy carbon black and white carbon black are dense and dust is avoided; aluminum silicate short fibers, polytetrafluoroethylene short fibers, micron-grade ceramic powder, and metal aluminum powder are dispersed in more paraffin wax as material B, which solves the problem that it is difficult to disperse the fibers directly added to rubber. Material A, material B, and EVA are extruded and granulated in a screw extruder, so that the wear-resistant filler and the heat-dissipating filler are dispersed and concentrated in the masterbatch. The wear-resistant and heat-dissipating masterbatch is directly added to the rubber during rubber mixing, and the masterbatch is easy to disperse in the rubber, avoiding the generation of dust at the mixing production site, which greatly facilitates production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional polymer materials, relates to functional rubber, and specifically relates to a wear-resistant heat-dissipating rubber masterbatch and a preparation method thereof. Background Art

[0002] As a durable material with toughness, elasticity and high strength, rubber is widely used in automobile tires, engineering machinery, aerospace, mechanical accessories, etc., such as seals, tires, conveyor belts, tracks, connectors, etc. The wear resistance and heat dissipation performance of rubber directly determine the service life of rubber products. If the wear resistance is reduced, the rubber product will be quickly damaged in the working conditions and even affect its use; if the heat dissipation performance is reduced, it will accelerate the aging of the rubber, thereby reducing the strength and wear resistance. Therefore, the comprehensive modification of rubber wear resistance and heat dissipation is extremely important to improve the service life of products and adaptability to the operating environment.

[0003] At present, in order to improve the wear resistance and heat dissipation of rubber, carbon black and white carbon black are mainly added for dispersion modification. Alumina, silicon carbide, boron nitride, metal powder, diamond powder, etc. are also used to improve the wear resistance and heat dissipation of rubber. However, since rubber is a viscoelastic material, it is mainly dispersed through mixing and processing, and the dispersion of powdered wear-resistant and heat-dissipating additives is poor. Especially for wear-resistant and heat-dissipating materials with a small amount of addition, if they are not fully dispersed, their wear resistance and heat dissipation effects will be affected.

[0004] China Invention Patent Publication No. CN114000147A discloses a wear-resistant rubber material and a preparation method. The wear-resistant rubber material includes a substrate, a transition layer and a functional layer; wherein the functional layer is a diamond film and a nitrogen-doped diamond-like film, and the diamond-like film and the nitrogen-doped diamond-like film are alternately deposited using vacuum pulse arc technology and nitrogen-assisted deposition to form a functional layer; finally, the nitrogen-doped diamond-like film is prepared as the outermost layer to improve the wear resistance of the rubber. Although this technology improves the wear resistance of the diamond-like film and the nitrogen-doped diamond-like film in the wear-resistant layer, the preparation process has high requirements and the preparation cost is high.

[0005] Chinese invention patent publication number CN111269470A discloses a wet-process wear-resistant rubber modified with silicone emulsion and a preparation method thereof. Through wet mixing, the binding effect between basic latex, carbon black filler, additives and other substances is effectively improved, and the dispersion effect of carbon black filler, additives and other substances in the basic latex is improved, and the finished product has high wear resistance.

[0006] China's invention patent publication number CN114230885A discloses a wear-resistant rubber formula for a wind turbine motor shaft, characterized in that the formula includes: a main material, a wear-resistant reinforcing material, a plasticizer, a reinforcing agent, an antioxidant, an active agent, and a vulcanizing material. By adding wear-resistant reinforcing materials Teflon and silicone oil to styrene-butadiene rubber and butadiene rubber, the wear resistance of the rubber is greatly improved, thereby improving the sealing effect of the wind turbine motor shaft.

[0007] Chinese invention patent publication number CN113444301A discloses a highly wear-resistant and heat-dissipating rubber and a preparation method thereof, wherein carbonization of polyacrylonitrile fiber and electroplating of metal are used for the wear-resistant and heat-dissipating treatment of the rubber.

[0008] Obviously, in terms of improving the wear resistance and heat dissipation performance of rubber, the selection and effective dispersion of materials are extremely important. The existing technology mainly adds the wear resistance and heat dissipation modifiers directly into the rubber matrix for kneading and mixing. For example, white carbon black and carbon black powders are fluffy and light, and produce a lot of dust when transported. If they are directly added to rubber for kneading, a large amount of dust will be generated; at the same time, due to the elasticity and viscosity of the rubber body, it becomes difficult to disperse the wear resistance and heat dissipation additives.

[0009] In order to facilitate industrial production and use, the wear-resistant and heat-dissipating additives are prepared into masterbatches in advance. This masterbatch is pre-dispersed and modified and made into granules, which will greatly facilitate transportation, production and use. Summary of the invention

[0010] In order to increase the dispersibility of wear-resistant and heat-dissipating additives in rubber and facilitate adding and dispersing in an internal mixer, the purpose of the present invention is to provide a method for preparing a wear-resistant and heat-dissipating rubber masterbatch, and further provide a wear-resistant and heat-dissipating rubber masterbatch. The wear-resistant and heat-dissipating rubber masterbatch prepared by the formula and method not only has excellent dispersibility in rubber, but also significantly improves the wear-resistant and heat-dissipating effect. A more significant effect is that the use of masterbatch greatly facilitates the rubber mixing process, reduces the dust generated by directly adding carbon black, white carbon black, etc. to rubber during mixing, and greatly improves the rubber mixing and mixing environment.

[0011] The present invention solves the technical problem by adopting the following technical solutions:

[0012] A method for preparing a wear-resistant and heat-dissipating rubber masterbatch, characterized in that it specifically comprises the following steps:

[0013] (1) Aromatic oil, carbon black and white carbon black are mixed and stirred in a mass ratio of 1:3-5:2 to make the carbon black and white carbon black dense and used as material A for standby use;

[0014] (2) Add aluminum silicate short fibers, polytetrafluoroethylene short fibers, micron-grade ceramic powder, metal aluminum powder, and paraffin wax into a mixer in a mass ratio of 1:1:3-5:2-3:3-4, and stir at 60-100° C. for 5-10 minutes to obtain material B for later use;

[0015] (3) Add material A, material B, and ethylene-vinyl acetate copolymer into a mixer in a mass ratio of 4:3:1, stir evenly at room temperature, and then send them into a screw extruder through an automatic elevator. The temperature of the screw extruder is set to: 40-50°C for the first section, 60-70°C for the second section, 80-90°C for the third section, 70-80°C for the fourth section, and 50-60°C for the fifth section; extrude into strips through the screw extruder, and air-cooled and pelletized to obtain a wear-resistant and heat-dissipating rubber masterbatch.

[0016] Aromatic oil is often used as a plasticizer and filler dispersant in rubber processing. Aromatic oil has good rubber compatibility and can significantly improve the processing properties of rubber. However, in actual use, aromatic oil, carbon black and rubber are mainly added to a mixer for mixing, resulting in carbon black dust, and limited aromatic oil permeates the rubber, which has limited dispersion of carbon black. In step (1), aromatic oil, carbon black and white carbon black are mixed and stirred in advance to allow carbon black and white carbon black to absorb aromatic oil, which not only makes carbon black and white carbon black dense and reduces dust, but also aromatic oil is fully contacted and dispersed with carbon black and white carbon black.

[0017] Preferably, the carbon black in step (1) is selected from one of N330, N220, and N234, and a compound of N330, N220, and N234 is further preferred.

[0018] Preferably, the white carbon black in step (1) is fumed white carbon black, which has high porosity and high specific surface area and has a reinforcing effect on rubber.

[0019] Aluminum silicate short fibers and polytetrafluoroethylene short fibers are difficult to disperse. By dispersing them with micron-grade ceramic powder and metal aluminum powder in a larger amount of paraffin wax, the dispersion of the fibers is solved, avoiding the problem of difficulty in dispersing the fibers when directly added to rubber.

[0020] Preferably, the aluminum silicate short fibers in step (2) have a length of 0.2-0.8 mm and an aspect ratio greater than 10. Aluminum silicate short fibers are resistant to acid and alkali corrosion and can be used in rubber to improve the wear resistance and reinforcement effect of rubber.

[0021] Preferably, the polytetrafluoroethylene short fibers in step (2) have a length of 0.5-1.5 mm and an aspect ratio greater than 10. Polytetrafluoroethylene short fibers are high in strength and corrosion-resistant and are used to improve the wear resistance and thermal stability of rubber.

[0022] Preferably, the micron-sized ceramic powder in step (2) is selected from one or a mixture of micron-sized silicon nitride powder, boron nitride powder, and alumina powder; further preferably, one or a mixture of silicon nitride powder, boron nitride powder, and alumina powder with a particle size less than 50 μm. Micron-sized ceramic powder can not only increase the wear resistance of rubber, but also has excellent heat dissipation, which can greatly improve the heat dissipation capacity of rubber, thereby adapting to timely heat dissipation of rubber during high-load sealing and high-load heat generation.

[0023] Preferably, the metal aluminum powder in step (2) is 200 mesh aluminum powder, mainly used as a heat dissipation auxiliary material.

[0024] Preferably, the stirring in step (2) is carried out at a low speed of 20-60 rpm. If the stirring speed is too high, the aluminum silicate short fibers and the polytetrafluoroethylene short fibers may be entangled and agglomerated.

[0025] Ethylene-vinyl acetate copolymer (EVA) as a carrier has good thermoplastic fluidity in the screw extruder, which is conducive to promoting the dispersion of material A and material B; ethylene-vinyl acetate copolymer also acts as a compatibilizer, promoting the dispersion of carbon black, white carbon black, micron ceramic powder, etc. with rubber; ethylene-vinyl acetate copolymer melts at a relatively low temperature (70-80°C), which can well adapt to the mixing temperature of rubber when in use.

[0026] Preferably, the screw extruder in step (3) is a parallel twin-screw extruder.

[0027] The present invention provides a wear-resistant and heat-dissipating rubber masterbatch prepared by the above method. Aromatic oil is used to pre-treat carbon black and white carbon black, so that the fluffy carbon black and white carbon black are compacted to avoid dust, and the aromatic oil is in full contact with carbon black and white carbon black, which is beneficial to the dispersion of carbon black and white carbon black; aluminum silicate short fibers, polytetrafluoroethylene short fibers, micron-grade ceramic powder, and metal aluminum powder are dispersed in more paraffin wax to solve the problem that it is difficult to disperse the fibers directly added to rubber. By extruding and granulating material A, material B and EVA in a screw extruder, the wear-resistant filler and the heat-dissipating filler are dispersed and concentrated in the masterbatch, and the masterbatch is directly added to the rubber during rubber mixing, so that the masterbatch is easy to disperse in the rubber, avoiding the generation of dust at the mixing production site, and greatly facilitating production.

[0028] Explanation of the beneficial effects of the present invention: In the processing of rubber, a mixer is often used to disperse various additives in the rubber. Since additives such as vulcanizers are added, in order to prevent premature cross-linking, the mixing temperature cannot be too high. The rubber mixing processing temperature is generally in the high elastic state-viscous flow state, usually below 100°C. It is difficult to disperse wear-resistant fillers and heat-dissipating fillers (carbon black, white carbon black, ceramic powder, metal powder, fiber, etc.) in the rubber by forced mixing in the high elastic state, and fluffy powders such as carbon black and white carbon black are very easy to generate dust, resulting in serious dust in the mixing environment. In view of this common problem in the field of rubber processing, the present invention proposes a technical idea of ​​pre-preparing wear-resistant additives and heat-dissipating additives into masterbatches, and adopts a preparation method of pre-treating and granulating wear-resistant fillers and heat-dissipating fillers with aromatic oil and paraffin when preparing wear-resistant and heat-dissipating rubber masterbatches; by dispersing carbon black and white carbon black, and dispersing aluminum silicate short fibers, polytetrafluoroethylene short fibers, and ceramic powder, a synergistic increase in wear resistance and heat dissipation effects is achieved. This technology is easy to implement, highly compatible with rubber processing, has a stable supply of raw materials, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Carbon black, white carbon black, short fibers, ceramic powder and other materials are prepared into masterbatches in advance, which greatly facilitates their use, as shown in the following figure:

[0030] Figure 1 This is a diagram of the wear-resistant and heat-dissipating rubber masterbatch prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to make those skilled in the art better understand the scheme of the present invention, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments. Based on the technical thinking of the present invention, other embodiments obtained by ordinary technicians in the field without making creative work should all belong to the scope of protection of the present invention. In the specific experimental examples, some raw materials and equipment that do not indicate specific brands and models are all conventional raw materials and equipment that can be obtained commercially. Unless otherwise specified, the raw materials used below are raw materials from the same batch.

[0032] Example 1

[0033] (1) Aromatic oil, carbon black (N234, N220, N330 are pre-mixed in a mass ratio of 3:2:1) and fumed silica in a mass ratio of 1:3:2 are mixed and stirred to make the carbon black and silica dense and used as material A for standby;

[0034] (2) Weigh aluminum silicate short fibers (length 0.2-0.8 mm, aspect ratio greater than 10), polytetrafluoroethylene short fibers (length 0.5-1.5 mm, aspect ratio greater than 10), boron nitride powder with a particle size less than 50 μm, 200 mesh aluminum powder, and 58# refined paraffin in a mass ratio of 1:1:3:2:3, add them into a mixer, stir at 80°C and 20 rpm for 10 min, and obtain material B for use;

[0035] (3) Material A, material B, and ethylene-vinyl acetate copolymer (EVA UL00328 Exxon Chemical) were added into a mixer in a mass ratio of 4:3:1, stirred evenly at room temperature, and then sent to a parallel twin-screw extruder via an automatic elevator. The temperature of the extruder was set as follows: 50°C for the first section, 70°C for the second section, 90°C for the third section, 70°C for the fourth section, and 50°C for the fifth section; the materials were extruded into strips through the parallel twin-screw extruder, and pelletized with air cooling to obtain a wear-resistant and heat-dissipating rubber masterbatch.

[0036] Example 2

[0037] (1) Aromatic oil, carbon black (N234, N220, N330 are pre-mixed in a mass ratio of 3:2:1) and fumed silica in a mass ratio of 1:4:2 are mixed and stirred to make the carbon black and silica dense and used as material A for standby;

[0038] (2) Weigh aluminum silicate short fibers (length 0.2-0.8 mm, aspect ratio greater than 10), polytetrafluoroethylene short fibers (length 0.5-1.5 mm, aspect ratio greater than 10), boron nitride powder with a particle size less than 50 μm, 200 mesh aluminum powder, and 58# refined paraffin wax in a mass ratio of 1:1:3:2:3, add them to a mixer, stir at 100°C and 60 rpm for 8 minutes, and obtain material B for use;

[0039] (3) Material A, material B, and ethylene-vinyl acetate copolymer (EVA UL00328 Exxon Chemical) were added into a mixer in a mass ratio of 4:3:1, stirred evenly at room temperature, and then sent to a parallel twin-screw extruder via an automatic elevator. The temperature of the extruder was set as follows: 50°C for the first section, 70°C for the second section, 90°C for the third section, 80°C for the fourth section, and 60°C for the fifth section; the materials were extruded into strips through the parallel twin-screw extruder, and pelletized with air cooling to obtain a wear-resistant and heat-dissipating rubber masterbatch.

[0040] Example 3

[0041] (1) Aromatic oil, carbon black (N234, N220, N330 are pre-mixed in a mass ratio of 3:2:1) and fumed silica in a mass ratio of 1:5:2 are mixed and stirred to make the carbon black and silica dense and used as material A for standby;

[0042] (2) Weigh aluminum silicate short fibers (length 0.2-0.8 mm, aspect ratio greater than 10), polytetrafluoroethylene short fibers (length 0.5-1.5 mm, aspect ratio greater than 10), silicon nitride powder with a particle size less than 50 μm, 200 mesh aluminum powder, and 58# refined paraffin wax in a mass ratio of 1:1:3:2:3, add them into a mixer, stir at 60°C and 20 rpm for 10 min, and obtain material B for use;

[0043] (3) Material A, material B, and ethylene-vinyl acetate copolymer (EVA UL00328 Exxon Chemical) were added into a mixer in a mass ratio of 4:3:1, stirred evenly at room temperature, and then sent to a parallel twin-screw extruder via an automatic elevator. The temperature of the extruder was set as follows: 50°C for the first section, 70°C for the second section, 90°C for the third section, 80°C for the fourth section, and 60°C for the fifth section; the materials were extruded into strips through the parallel twin-screw extruder, and pelletized with air cooling to obtain a wear-resistant and heat-dissipating rubber masterbatch.

[0044] Example 4

[0045] (1) Aromatic oil, carbon black (N234, N220, N330 are pre-mixed in a mass ratio of 3:2:1) and fumed silica in a mass ratio of 1:3:2 are mixed and stirred to make the carbon black and silica dense and used as material A for standby;

[0046] (2) Weigh aluminum silicate short fibers (length 0.2-0.8 mm, aspect ratio greater than 10), polytetrafluoroethylene short fibers (length 0.5-1.5 mm, aspect ratio greater than 10), boron nitride powder with a particle size less than 50 μm, 200 mesh aluminum powder, and 58# refined paraffin wax in a mass ratio of 1:1:4:2:3, add them into a mixer, stir at 100°C and 60 rpm for 5 minutes, and obtain material B for use;

[0047] (3) Material A, material B, and ethylene-vinyl acetate copolymer (EVA UL00328 Exxon Chemical) were added into a mixer in a mass ratio of 4:3:1, stirred evenly at room temperature, and then sent to a parallel twin-screw extruder via an automatic elevator. The temperature of the extruder was set as follows: 50°C for the first section, 70°C for the second section, 90°C for the third section, 80°C for the fourth section, and 60°C for the fifth section; the materials were extruded into strips through the parallel twin-screw extruder, and pelletized with air cooling to obtain a wear-resistant and heat-dissipating rubber masterbatch.

[0048] Example 5

[0049] (1) Aromatic oil, carbon black (N234, N220, N330 are pre-mixed in a mass ratio of 3:2:1) and fumed silica in a mass ratio of 1:3:2 are mixed and stirred to make the carbon black and silica dense and used as material A for standby;

[0050] (2) Weigh aluminum silicate short fibers (length 0.2-0.8 mm, aspect ratio greater than 10), polytetrafluoroethylene short fibers (length 0.5-1.5 mm, aspect ratio greater than 10), boron nitride powder with a particle size less than 50 μm, 200 mesh aluminum powder, and 58# refined paraffin wax in a mass ratio of 1:1:5:2:3, add them into a mixer, stir at 100°C and 60 rpm for 5 minutes, and obtain material B for use;

[0051] (3) Material A, material B, and ethylene-vinyl acetate copolymer (EVA UL00328 Exxon Chemical) were added into a mixer in a mass ratio of 4:3:1, stirred evenly at room temperature, and then sent to a parallel twin-screw extruder via an automatic elevator. The temperature of the extruder was set as follows: 40°C for the first section, 70°C for the second section, 80°C for the third section, 80°C for the fourth section, and 60°C for the fifth section; the materials were extruded into strips through the parallel twin-screw extruder, and pelletized with air cooling to obtain a wear-resistant and heat-dissipating rubber masterbatch.

[0052] Comparative Example 1

[0053] (1) Aromatic oil, carbon black (N234, N220, N330 are pre-mixed in a mass ratio of 3:2:1) and fumed silica in a mass ratio of 1:3:2 are mixed and stirred to make the carbon black and silica dense and used as material A for standby;

[0054] (2) Weigh aluminum silicate short fibers (length 0.2-0.8 mm, aspect ratio greater than 10), boron nitride powder with a particle size less than 50 μm, 200 mesh aluminum powder, and 58# refined paraffin wax in a mass ratio of 2:3:2:3, add them into a mixer, stir at 80°C and 20 rpm for 10 min, and obtain material B for use;

[0055] (3) Material A, material B, and ethylene-vinyl acetate copolymer (EVA UL00328 Exxon Chemical) were added into a mixer in a mass ratio of 4:3:1, stirred evenly at room temperature, and then sent to a parallel twin-screw extruder via an automatic elevator. The temperature of the extruder was set as follows: 50°C for the first section, 70°C for the second section, 90°C for the third section, 70°C for the fourth section, and 50°C for the fifth section; the materials were extruded into strips through the parallel twin-screw extruder, and pelletized with air cooling to obtain a wear-resistant and heat-dissipating rubber masterbatch.

[0056] Comparative Example 2

[0057] (1) Aromatic oil, carbon black (N234, N220, N330 are pre-mixed in a mass ratio of 3:2:1) and fumed silica in a mass ratio of 1:3:2 are mixed and stirred to make the carbon black and silica dense and used as material A for standby;

[0058] (2) Weigh aluminum silicate short fibers (length 0.2-0.8 mm, aspect ratio greater than 10), polytetrafluoroethylene short fibers (length 0.5-1.5 mm, aspect ratio greater than 10), boron nitride powder with a particle size less than 50 μm, 200 mesh aluminum powder, and 58# refined paraffin in a mass ratio of 1:1:3:2:1, add them into a mixer, stir at 80°C and 20 rpm for 10 min, and obtain material B for use;

[0059] (3) Material A, material B, and ethylene-vinyl acetate copolymer (EVA UL00328 Exxon Chemical) were added into a mixer in a mass ratio of 4:3:1, stirred evenly at room temperature, and then sent to a parallel twin-screw extruder via an automatic elevator. The temperature of the extruder was set as follows: 50°C for the first section, 70°C for the second section, 90°C for the third section, 70°C for the fourth section, and 50°C for the fifth section; the materials were extruded into strips through the parallel twin-screw extruder, and pelletized with air cooling to obtain a wear-resistant and heat-dissipating rubber masterbatch.

[0060] Comparative Example 3

[0061] (1) Aromatic oil, carbon black (N234, N220, N330 are pre-mixed in a mass ratio of 3:2:1) and fumed silica in a mass ratio of 0.5:3:2 are mixed and stirred to make the carbon black and silica dense and used as material A for standby;

[0062] (2) Weigh aluminum silicate short fibers (length 0.2-0.8 mm, aspect ratio greater than 10), polytetrafluoroethylene short fibers (length 0.5-1.5 mm, aspect ratio greater than 10), boron nitride powder with a particle size less than 50 μm, 200 mesh aluminum powder, and 58# refined paraffin in a mass ratio of 1:1:3:2:3, add them into a mixer, stir at 80°C and 20 rpm for 10 min, and obtain material B for use;

[0063] (3) Material A, material B, and ethylene-vinyl acetate copolymer (EVA UL00328 Exxon Chemical) were added into a mixer in a mass ratio of 4:3:1, stirred evenly at room temperature, and then sent to a parallel twin-screw extruder via an automatic elevator. The temperature of the extruder was set as follows: 50°C for the first section, 70°C for the second section, 90°C for the third section, 70°C for the fourth section, and 50°C for the fifth section; the materials were extruded into strips through the parallel twin-screw extruder, and pelletized with air cooling to obtain a wear-resistant and heat-dissipating rubber masterbatch.

[0064] Comparative Example 4

[0065] (1) Aromatic oil, carbon black (N234, N220, N330 are pre-mixed in a mass ratio of 3:2:1) and fumed silica in a mass ratio of 1:3:2 are mixed and stirred to make the carbon black and silica dense and used as material A for standby;

[0066] (2) Weigh aluminum silicate short fibers (length 0.2-0.8 mm, aspect ratio greater than 10), polytetrafluoroethylene short fibers (length 0.5-1.5 mm, aspect ratio greater than 10), 200 mesh aluminum powder, and 58# refined paraffin wax in a mass ratio of 1:1:2:3, add them into a mixer, stir at 80°C and 20 rpm for 10 min, and obtain material B for use;

[0067] (3) Material A, material B, and ethylene-vinyl acetate copolymer (EVA UL00328 Exxon Chemical) were added into a mixer in a mass ratio of 4:3:1, stirred evenly at room temperature, and then sent to a parallel twin-screw extruder via an automatic elevator. The temperature of the extruder was set as follows: 50°C for the first section, 70°C for the second section, 90°C for the third section, 70°C for the fourth section, and 50°C for the fifth section; the materials were extruded into strips through the parallel twin-screw extruder, and pelletized with air cooling to obtain a wear-resistant and heat-dissipating rubber masterbatch.

[0068] Wear resistance test comparison:

[0069] The wear-resistant heat-dissipating rubber masterbatch obtained by adjusting the embodiment and the comparative example of the formula is used for internal mixing. 30% of the masterbatch, 64% of butadiene rubber, 4% of sulfur, and 2% of the accelerator CZ are added to the internal mixing machine for internal mixing for 6 minutes, and then the sheet is produced, and the thickness of the sheet is controlled at 4mm. The test sample is vulcanized for 10 minutes under the conditions of 160°C and 8MPa on a flat vulcanizer, and the sample is cut with reference to GB / T 1689-2014 (Determination of wear resistance of vulcanized rubber) to test the wear resistance. The wear resistance of the rubber is represented by the wear amount of 1.61km. The higher the wear value, the worse the wear resistance. The test results are shown in Table 1.

[0070] Cooling effect test comparison:

[0071] The thermal conductivity of the vulcanized rubber was measured by the guarded heat plate method, and the heat dissipation effect of the rubber was evaluated by the thermal conductivity. The higher the thermal conductivity, the better the heat dissipation effect. The test data is shown in Table 1.

[0072] Table 1

[0073]

[0074] Through the above test comparison, the wear-resistant heat-dissipating rubber masterbatch of the present invention can be easily added to rubber for mixing, and the prepared rubber has excellent wear resistance and heat dissipation. In the comparative example 1 of the experimental scheme, the formula was adjusted, and polytetrafluoroethylene short fibers were not added. The wear value of the rubber was high and the wear resistance decreased, indicating that the polytetrafluoroethylene short fibers played an outstanding role in increasing the wear resistance of rubber; in the comparative example 2 of the experimental scheme, when processing the fibers, the amount of paraffin was greatly reduced, and the fibers were easily entangled, which affected the subsequent dispersion, and affected the dispersion of aluminum silicate short fibers and polytetrafluoroethylene short fibers in the rubber, affecting the wear resistance. Therefore, the present invention has an outstanding effect of pre-dispersing the fibers with more paraffin; in the comparative example 3 of the experimental scheme, the amount of aromatic oil was greatly reduced, which affected the dispersion of carbon black and white carbon black, thereby having a certain effect on the wear resistance; in the comparative example 4 of the experimental scheme, the formula was adjusted, and boron nitride powder was not added. The masterbatch used in rubber will affect the heat dissipation effect.

[0075] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered as exemplary and non-restrictive in all respects.

Claims

1. A method for preparing a wear-resistant and heat-dissipating rubber masterbatch, characterized in that: The specific steps include: (1) Aromatic oil, carbon black and white carbon black are mixed and stirred in a mass ratio of 1:3-5:2 to make the carbon black and white carbon black dense and used as material A for standby use; (2) Add aluminum silicate short fibers, polytetrafluoroethylene short fibers, micron-grade ceramic powder, metal aluminum powder, and paraffin into a mixer in a mass ratio of 1:1:3-5:2-3:3-4, and stir at 60-100° C. for 5-10 minutes to obtain material B for standby use; the aluminum silicate short fibers have a length of 0.2-0.8 mm and an aspect ratio of greater than 10; the polytetrafluoroethylene short fibers have a length of 0.5-1.5 mm and an aspect ratio of greater than 10; (3) Add material A, material B, and ethylene-vinyl acetate copolymer into a mixer in a mass ratio of 4:3:1, stir evenly at room temperature, and then send them into a screw extruder through an automatic elevator. The temperature of the screw extruder is set to: 40-50°C for the first section, 60-70°C for the second section, 80-90°C for the third section, 70-80°C for the fourth section, and 50-60°C for the fifth section; extrude into strips through the screw extruder, and air-cooled and pelletized to obtain a wear-resistant and heat-dissipating rubber masterbatch.

2. The method for preparing the wear-resistant and heat-dissipating rubber masterbatch according to claim 1, characterized in that: The carbon black in step (1) is selected from one or more of N330, N220, and N234.

3. The method for preparing the wear-resistant and heat-dissipating rubber masterbatch according to claim 1, characterized in that: The white carbon black in step (1) is selected from fumed white carbon black.

4. The method for preparing the wear-resistant and heat-dissipating rubber masterbatch according to claim 1, characterized in that: The micron-sized ceramic powder in step (2) is selected from one or a mixture of micron-sized silicon nitride powder, boron nitride powder, and aluminum oxide powder.

5. The method for preparing the wear-resistant and heat-dissipating rubber masterbatch according to claim 1, characterized in that: The metal aluminum powder in step (2) is 200 mesh aluminum powder.

6. The method for preparing the wear-resistant and heat-dissipating rubber masterbatch according to claim 1, characterized in that: The stirring in step (2) is carried out at a low speed of 20-60 rpm.

7. The method for preparing the wear-resistant and heat-dissipating rubber masterbatch according to claim 1, characterized in that: The screw extruder described in step (3) is a parallel twin-screw extruder.

8. A wear-resistant and heat-dissipating rubber masterbatch, characterized in that: The method is prepared by any one of claims 1 to 7.

Citation Information

Patent Citations

  • Organosilicon emulsion modified wet-process wear-resistant rubber and preparation method thereof

    CN111269470A

  • High-wear-resistance heat dissipation rubber and preparation method thereof

    CN113444301A

  • Wear-resistant rubber material and preparation method thereof

    CN114000147A

  • Wear-resistant rubber formula for wind power motor shaft and preparation method of wear-resistant rubber formula

    CN114230885A

  • Ultrafine fly ash reinforced styrene butadiene rubber and preparation method thereof

    CN106496698A